Survey of employment tribunal applications, 2013 (UK Data Service, 2015)
The Survey of Employment Tribunal Applications (SETA) series aims to provide information on the characteristics of the parties in, and the key features of, employment tribunal cases. The headline aims of the 2018 study were to: get information on the characteristics of employment tribunal claimants and employers; assess the costs of going to tribunals for claimants and employers; and monitor the performance of the employment tribunal claim process. The first SETA was undertaken in 1987, with subsequent surveys undertaken in 1992, 1998, 2003, 2008 and 2013. The survey methodology used in 2018 was very similar to that used in 2013. A total of 2,663 interviews were carried out; 1,373 interviews with claimants and 1,290 with employers. The average interview length in the claimant survey was 30 minutes and in the employer survey 26 minutes. Further information may be found on the gov.uk Survey of Employment Tribunal Applications 2018 webpage. This is the seventh survey in a series dating back to 1987. The 1998, 2003, 2008 and 2013 surveys (SNs 4894, 6714, 5022 and 7727 respectively) are available at the UK Data Service.